Floodplain soils on the soil map of the Russian Federation, scale 1 : 2.5 M, 1988, in the Russian soil classification - N. V. Savitskaya; T. V. Ananko; M. I. Gerasimova (Бюллетень Почвенного института им. В.В. Докучаева, 2021)
The development of the digital model of the soil map of Russia derived of the map of the Soviet Russian Federation, 1988, compiled in Dokuchaev Soil Science Institute, comprises the transfer of soil names in the initial legend to those in the new classification system of Russian soils (2004). Floodplain soils (only native) are represented by seven legend units (out of 205) that were named in terms of soil classification of USSR, 1977, and part of their names indicated ‘landscapes’ rather than soils, which disagrees with the principles of the new classification system. Basing on numerous publications and following the rules of the new system, soils were renamed. Most of them were referred to alluvial soil types within the synlithogenic trunk (Fluvisols), and their new names indicate both their properties and their zonal attachment. In order to obtain more adequate patterns of soils in river valleys additional soils were introduced including stratified-alluvial soils in the trunk of primary pedogenesis (Regosols). Simultaneously, the composition of polygons in the database was revised in accordance with regional data; human-modified soils were introduced (agro-soils and urbo-soils).